Del trineo a la postmodernidad: Dene, Inuit y Métis en la sociedad canadiense actual - Valladares Fernández, Secundino; Junquera Rubio, Carlos (Revista Española de Antropología Americana, 2001)
This essay deals with the basic claims posed by the autocthonous groups of Déné, Inuit and Métis to the Canadian government. To that effect, this paper analyses some of the strategies and processes through which these Canadian autocthonous groups are able to become a postmodern society, to enjoy a goad quality of life , and to reach a lifestyle far away from their more recent past. The typical markers of their recent history such as the dog, the canoe and the sled have vanished to become shades of the past. A positive legislation and a new mentality among the social actors have been crucial to explain this dramatic change.